2011
DOI: 10.1007/s00424-011-0997-3
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of P2Y receptors mediating ATP induced relaxation in guinea pig airway smooth muscle: involvement of prostaglandins and K+ channels

Abstract: In airway smooth muscle (ASM), adenosine 5'-triphosphate (ATP) induces a relaxation associated with prostaglandin production. We explored the role of K(+) currents (I (K)) in this relaxation. ATP relaxed the ASM, and this effect was abolished by indomethacin. Removal of airway epithelium slightly diminished the ATP-induced relaxation at lower concentration without modifying the responses to ATP at higher concentrations. ATPγS and UTP induced a concentration-dependent relaxation similar to ATP; α,β-methylene-AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 33 publications
(64 reference statements)
4
23
0
Order By: Relevance
“…B). A negative control for P2Y 2 receptor with its blocking peptide was already carried out in a previous work (16). With respect to alkaline phosphatase, confocal images showed that activity of this enzyme was minimal in airway epithelium from nonsensitized guinea pigs (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…B). A negative control for P2Y 2 receptor with its blocking peptide was already carried out in a previous work (16). With respect to alkaline phosphatase, confocal images showed that activity of this enzyme was minimal in airway epithelium from nonsensitized guinea pigs (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…TEA (1-30 mM) did not inhibit androgen-induced relaxation. Because TEA blocks K v and BK Ca, which are the most important K C channels in ASM (Montaño et al 2011), it can be concluded that they do not participate in the androgen-induced relaxation. In addition, the possibility that the b 2 -adrenoceptors are involved in the relaxation to 5a-DHT or DHEA (Bordallo et al 2008, Espinoza et al 2013, as well as the polyamine synthesis in the relaxation induced by 5a-DHT (Bordallo et al 2008), has been eliminated.…”
Section: Androgens Relaxing Mechanismmentioning
confidence: 99%
“…High levels of prostanoids in bronchoalveolar lavage fluid and the increased expression of COX-2 in lung tissue have been detected in subjects with asthma (18). PGE 2 is produced by airway epithelial cells (19)(20)(21) and by smooth muscle cells (22)(23)(24)(25), and has been demonstrated to regulate airway caliber (26)(27)(28). There are four subtypes of PGE 2 receptors: EP 1-4 .…”
mentioning
confidence: 99%